BIMBINGAN POLA ASUH ANAK BAGI ORANG TUA BERDASARKAN AL-QURAN DAN ASSUNAH - Cucu Arumsari; Milah Nurkamilah; Feida Noorlaila Isti’adah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The main factors that support the success of children start from the family than a school, community, and daily relationships. The primary foundation of children's education is the guidance and training of parents from childhood to adulthood. Therefore, parents need a good understanding of how to educate children. Society of Sukahurip, Tamansari, Tasikmalaya are predominantly Muslim. Parents' attention to the development of their children still considered not optimal; most of their time spent working. Therefore, active guidance for parents to be able to guide their children maximally is still needed. This community service is one of the efforts to help parents gain knowledge in educating children who are kind and right according to Islam following the Koran and Hadith.